Indirect stress and air-cavity displacement measurement of MEMS tunable VCSELs via micro-Raman and micro-photoluminescence spectroscopy. (28th January 2022) - Tingzon, Philippe Martin; Husay, Horace Andrew; Cabello, Neil Irvin; Eslit, John Jairus; Cook, Kevin; Kapraun, Jonas; Somintac, Armando; De Leon, Maria Theresa; Rosales, Marc; Salvador, Arnel; Chang-Hasnain, Constance; Estacio, Elmer
Abstract: We employ micro-Raman spectroscopy to optically infer the stress experienced by the legs of a bridge-type microelectromechanical systems (MEMS) used in high contrast gratings tunable vertical cavity surface emitting lasers (VCSELs). We then employ micro-photoluminescence (PL) spectroscopy to indirectly measure the air cavity displacement of the same MEMS structure. Results from micro-Raman showed that electrostatically actuating the MEMS with a DC bias configuration yields increasing residual stress on the endpoints of the MEMS with values reaching up to 0.8 GPa. We simulated a finite element model via Comsol Multiphysics which agrees with the trend we observed based on our micro-Raman data. Our micro-PL spectroscopy showed that change in the air cavity of the VCSEL structure resulted in a change in the full width of the PL peak emitted by the layer consisting of four pairs of distributed Bragg reflectors. The change in the full width of the PL peak was due to the change in the optical cavity induced by displacing the MEMS via externally applied bias and agrees with our transfer matrix convolution simulation. These optical characterization tools can be used for failure analysis, MEMS design improvements, and monitoring of MEMS tunable VCSEL devices for mass production and manufacturing.